2007
DOI: 10.1016/j.jcrs.2006.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Three-hundred-sixty degree barrier effect of a square-edged and an enhanced-edge intraocular lens on centripetal lens epithelial cell migration

Abstract: This study showed the barrier effect of the edge design of the C-flex IOL and the efficacy of the enhanced edge in preventing LEC migration at the optic-haptic junction. The enhanced edge was as effective as a sharp square edge in restricting the LEC migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…These factors may have correlation with PCO formation as suggested in literature. 34,35 The results of this study reinforce the already known fact that hydrophobic IOLs have low incidence of PCO compared to hydrophilic, and hence should be preferred. Since most of the hydrophobic acrylic IOLs currently available are designed to have a square optic edge, this should be an ideal combination further reducing the chances of PCO.…”
Section: Discussionsupporting
confidence: 83%
“…These factors may have correlation with PCO formation as suggested in literature. 34,35 The results of this study reinforce the already known fact that hydrophobic IOLs have low incidence of PCO compared to hydrophilic, and hence should be preferred. Since most of the hydrophobic acrylic IOLs currently available are designed to have a square optic edge, this should be an ideal combination further reducing the chances of PCO.…”
Section: Discussionsupporting
confidence: 83%
“…It is well documented that IOL edge design is an important factor in the pathogenesis of PCO and that a square-edged optic (as in the IOL we used) results in a lower PCO rate than a round-edged optic. 18,19, In conclusion, based on our evaluation of postoperative visual outcomes, we conclude that the M-flex 630F C3 refractive multifocal IOL is an effective alternative to monofocal IOLs and provides excellent distance and intermediate vision, sufficient functional near vision, good contrast sensitivity, and a low incidence of visual disturbances and PCO remain. We recommend studies of whether a model with a C4.00 D add would improve the near-vision performance of this IOL.…”
Section: Discussionmentioning
confidence: 67%
“…The IOL has a 360-degree square edge to prevent lens epithelial cell migration and thus posterior capsule opacification (PCO). 18,19 The IOL material is a proprietary hydrophilic acrylic copolymer with an ultraviolet (UV) light filter. The water content is 26% and the refractive index, 1.46.…”
Section: Intraocular Lensmentioning
confidence: 99%
“…Rabbit and clinical studies found a better barrier effect against lens epithelial cell (LEC) migration with this design than with the earlier version (model 570H) with a smooth optic-haptic transition. 6,[21][22][23] The study IOL evaluated in our study has loops that are thinner close to the optic-haptic junctions, creating beveled barrier steps anteriorly and posteriorly to enhance prevention of cell migration/proliferation toward the visual axis. Even though PCO started at the level of the optic-haptic junctions in 3 of 5 eyes with the study IOL (versus 4 of 5 control eyes), significantly less PCO was observed in the study eyes at the end of the follow-up period.…”
Section: Discussionmentioning
confidence: 99%